2022
DOI: 10.1002/gps.5826
|View full text |Cite
|
Sign up to set email alerts
|

Survival and causes of death among people with clinically diagnosed dementia with Lewy bodies: A multicenter cohort study

Abstract: Objective A comprehensive study of the survival and causes of death of people with clinically diagnosed Dementia with Lewy bodies (DLB) were few. The aim of our study was to investigate the survival and causes of death of DLB. Methods The patients diagnosed with probable DLB were consecutively enrolled from five memory clinics in China across a 5‐year period (2017–2021) with mortality data updated to December 2021. The endpoint was all‐cause death. Survival analysis including Cox regression by groups (time bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the recent study in patients with probable DLB enrolled from memory clinics in China, use of anti‐psychotics predicted a shorter survival 24 . Previous studies have identified cognitive impairment 29 or dementia 30 and symptoms of psychosis such as hallucinations 31 in Parkinson's disease as risk factors for death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent study in patients with probable DLB enrolled from memory clinics in China, use of anti‐psychotics predicted a shorter survival 24 . Previous studies have identified cognitive impairment 29 or dementia 30 and symptoms of psychosis such as hallucinations 31 in Parkinson's disease as risk factors for death.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, categories such as aspiration pneumonia and genitourinary causes of death reflect mechanisms which are potentially influenced by treatment in a patient with dementia and potentially modifiable. In a recent study in patients with probable DLB enrolled from memory clinics in China, cause of death was as reported by the family or from medical records 24 rather than ICD codes, with categories including failure to thrive (stopped eating or drinking) and multiorgan failure in addition to pneumonia or aspiration. Direct comparison of cause of death results with our study is therefore limited, due to a different assignment of death categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reality accommodates this consequence in those empirical findings on the basis of which it has been concluded that failure to thrive may be the most common cause of death in patients diagnosed with dementia, similar to the multiple organ dysfunction syndrome and more common than the respiratory failure that is attributed to infection in those who are diagnosed with pneumonia. 13 The most durable mechanism of recovery in humans reduces the consequences of severity precipitation by increasing cellular hemoglobin It follows that even after discharge has been permitted by insult abatement, increased severity of the underlying pathology may once again be precipitated by another insult. Reality accommodates this consequence in those empirical findings of Nekooghadam et al in a 61-yearold patient whose returning results, upon presenting again after being discharged following near complete resolution of the signs and symptoms which were attributed to COVID-19 infection 3 weeks earlier, revealed a dramatic fall in hemoglobin and platelet count compared to values recorded on the discharge notes instead of nasopharyngeal swab positivity.…”
Section: Long Covid and Other "Post-acute" Conditions Are Due To Abat...mentioning
confidence: 99%